Monty Python and the Holy Grail [videorecording (DVD)] - Gilliam, Terry; Jones, Terry, 1942-2020-; Chapman, Graham, 1941-1989; Cleese, John; Idle, Eric; Palin, Michael (Columbia TriStar Home Entertainment, 2001)
The quest for the Holy Grail by King Arthur and his Knights of the Round Table is retold in the inimitable Python fashion.